PROBLEMATIKA PEMBELAJARAN DARING MASA PANDEMI MATA PELAJARAN GEOGRAFI KELAS X SMA NEGERI 6 PONTIANAK - Leony Dwiyana; Nuraini Asriati; Nur Meily Adlika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to discover online learning problems and the efforts made during the Covid-19 pandemic in class XI geography subjects at SMA Negeri 6 Pontianak. The research method used is descriptive with a qualitative approach. This study's data sources were interviews with the principal, geography subject teachers, and several tenth- grade students at SMA Negeri 6 Pontianak. The results showed that online learning problems in geography subjects in class X SMA Negeri 6 Pontianak were a lack of motivation, concentration, and student learning outcomes during online learning. In addition, the limitations of supporting facilities and infrastructure for students and teachers. Efforts made to overcome the problems are the school providing internet data quota facilities and borrowing school computer laboratories for students or teachers who do not have or are having problems with devices that support the learning process.